PHYTOCHEMICAL SCREENING AND GC-MS ANALYSIS OF APIUM GRAVEOLENS L. SEED EXTRACTS. - SHANMUGAPRIYA.R; USHADEVI.T (International Journal of Pharma and Bio Sciences, 2015)
Apium graveolens is commonly known as an celery used by the traditional practitioners as antibiotic, anticancer, antidiabetic and reducer for cholesterol, fever and blood pressure. The present study aims to screen the phytochemical compounds from A.graveolens seed extracts and characterize the phytochemical compounds by Gas-Chromatography and Mass Spectrometric (GC-MS) analysis. Qualitative phytochemical compounds were analyzed by using methanol and diethyl ether extracts of the plant seeds. The results revealed the presence of amino acids, alkaloids, carbohydrates, glycosides, flavonoids, phenol, saponins, steroids, tannins and terpenoids in those two extracts. Chromatogram of GC-MS analysis of the methanolic extract showed the presence of 10 compounds and Diethyl ether extracts showed 8 compounds.